The Indian Council of Agricultural Research (ICAR) prioritized nutrition in breeding by establishing minimum levels of iron and zinc to breed in pearl millet - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
In 2018, the Indian Council on Agriculture Research established minimum levels of iron and zinc for their pearl millet breeding program, levels informed by joint research with CGIAR. This change means that all future releases of pearl millet varieties in India will be more nutritious and iron and zinc intake will improve among pearl millet consuming populations.